Odpowiedź :
Odpowiedź:
[tex]a)\ \ 2x+y=7[/tex]
Wyznaczamy niewiadomą x
[tex]2x+y=7\\\\2x=7-y\ \ /:2\\\\y=\frac{7}{2}-\frac{y}{2}\\\\y=\frac{7}{2}-\frac{1}{2}y[/tex]
Wyznaczamy niewiadomą y
[tex]2x+y=7\\\\y=7-2x\\\\\\b)\ \ x-y=3[/tex]
Wyznaczamy niewiadomą x
[tex]x-y=3\\\\x=3+y[/tex]
Wyznaczamy niewiadomą y
[tex]x-y=3\\\\-y=3-x\ \ /\cdot(-1)\\\\y=-3+x[/tex]
[tex]c)\ \ \frac{1}{6}y=x+2[/tex]
Wyznaczamy niewiadomą x
[tex]\frac{1}{6}y=x+2\\\\-x=2-\frac{1}{6}y\ \ /\cdot(-1)\\\\x=-2+\frac{1}{6}y[/tex]
Wyznaczamy niewiadomą y
[tex]\frac{1}{6}y=x+2\ \ /\cdot6\\\\y=6x+12\\\\\\d)\ \ 4(x-y)=3x[/tex]
Wyznaczamy niewiadomą x
[tex]4(x-y)=3x\\\\4x-4y=3x\\\\4x-3x=4y\\\\x=4y[/tex]
Wyznaczamy niewiadomą y
[tex]4(x-y)=3x\\\\4x-4y=3x\\\\-4y=3x-4x\\\\-4y=-x\ \ /:(-4)\\\\y=\frac{1}{4}x[/tex]
[tex]e)\ \ \frac{4}{5}x=\frac{2}{3}y[/tex]
Wyznaczamy niewiadomą x
[tex]\frac{4}{5}x=\frac{2}{3}y\ \ /\cdot5\\\\4x=\frac{10}{3}y\ \ /:4\\\\x=\frac{\not10^5}{3}y\cdot\frac{1}{\not4_{2}}\\\\x=\frac{5}{6}y[/tex]
Wyznaczamy niewiadomą y
[tex]\frac{4}{5}x=\frac{2}{3}y\\\\\frac{2}{3}y=\frac{4}{5}x\ \ /:\frac{2}{3}\\\\y=\frac{\not4^2}{5}x\cdot\frac{3}{\not2_{1}}}\\\\y=\frac{6}{5}x\\\\\\f)\ \ 8x+4y=12[/tex]
Wyznaczamy niewiadomą x
[tex]8x+4y=12\ \ /:4\\\\2x+y=3\\\\2x=3-y\ \ /:2\\\\x=\frac{3}{2}-\frac{1}{2}y[/tex]
Wyznaczamy niewiadomą y
[tex]8x+4y=12\ \ /:4\\\\2x+y=3\\\\y=3-2x[/tex]
Odpowiedź:
Szczegółowe wyjaśnienie:
a)
[tex]2x+y=7/-2x\\y=7-2x[/tex]
[tex]2x+y=7/-y\\2x=7-y/:2\\x=\frac{7-y}{2}[/tex]
b)
[tex]x-y=3/+y\\x=3+y[/tex]
[tex]x-y=3/-x\\-y=3-x/:(-1)\\y=-3+x\\y=x-3[/tex]
c)
[tex]\frac{1}{6} y=x+2/*6\\y=6x+12[/tex]
[tex]\frac{1}{6} y=x+2\\x+2=\frac{1}{6} y/-2\\x=\frac{1}{6} y-2[/tex]
d)
[tex]4(x-y)=3x\\4x-4y=3x\\4x-3x=4y\\x=4y[/tex]
[tex]4(x-y)=3x\\4x-4y=3x/-4x\\-4y=3x-4x\\-4y=-x/:(-4)\\y=\frac{x}{4}[/tex]
e)
[tex]\frac{4}{5}x=\frac{2}{3} y/*\frac{5}{4} \\x=\frac{2}{3} y*\frac{5}{4} \\x=\frac{10}{12} y\\x=\frac{5}{6} y[/tex]
[tex]\frac{4}{5} x=\frac{2}{3} y\\\frac{2}{3} y=\frac{4}{5}x/*\frac{3}{2} \\y=\frac{4}{5} x*\frac{3}{2} \\y=\frac{12}{10} x\\y=\frac{6}{5}y[/tex]
f)
[tex]8x+4y=12/-4y\\8x=12-4y/:8\\x=\frac{12}{8} -\frac{4}{8} y\\x=\frac{3}{2} -\frac{1}{2}y[/tex]
[tex]8x+4y=12/-8x\\4y=12-8x/:4\\y=3-2x[/tex]